Perancangan Sistem Informasi Reservasi Sewa Kamar Hotel Berbasis Web (Studi Kasus Hotel Kharisma Rangkasbitung) - Nursofa Putri Pratama Nursofa; Bagas Setiyaki Wicaksono (CV. Multi Kreasi Media, 2022)
Hotel Kharisma RangkasBitung is one of the hotels that still uses manual methods or there is no computerized system that processes all room rental data. This is felt to be less effective and inefficient, because if there is an additional room rental data, it must be detailed as a whole, thus providing ineffectiveness in data processing and data storage. The impact of this problem is the delay in reporting to the hotel owner. To overcome this problem, the hotel needs a form of web-based hotel room rental reservation information system that can assist in processing data and storing hotel room rental data, especially regarding hotel room rental data and every time it is updated to ensure the data is fixed and accurate, in order to obtain satisfactory data.